Yeast interaction on Chardonnay wine composition: Impact of strain and inoculation time. (16th April 2022) - Roullier-Gall, C.; Bordet, F.; David, V.; Schmitt-Kopplin, P.; Alexandre, H.
Highlights: Every species can be described by a unique pattern of metabolites reflecting major differences between species regarding yeast metabolism. S. cerevisiae is characterized by a metabolic richness not found with non- Saccharomyces yeasts. The dominance of Saccharomyces cerevisiae is dependent on inoculation time and on the other species present. Co-inoculation leads to the formation of new compounds, reflecting a reshuffling of yeast metabolism linked to interaction mechanisms. Metabolomic analysis unravels changes in nitrogen metabolism due to yeast-yeast interactions. Abstract: It is of great importance to understand the molecular characteristics and substantial chemical transformations due to yeast-yeast interaction. Non-targeted metabolomics was used to unravel must in fermentation composition, inoculated with non- Saccharomyces ( NS ) yeasts and Saccharomyces cerevisiae ( S ) for sequential fermentation. ultrahigh-resolution mass spectrometry was able to distinguish thousands of metabolites and provides deep insights into grape must composition allowing better understanding of the yeast-yeast interactome. The dominance of S, characterized by a metabolic richness not found with NS, is dependent on inoculation time and on the yeast species present. Co-inoculation leads to the formation of new compounds, reflecting a reshuffling of yeast metabolism linked to interaction mechanisms. Among the modifications observed, metabolomic unravels deep changes in nitrogen metabolism due to yeast-yeast interactions and suggests that the redistribution pattern affects two different routes, the pentose phosphate and the amino acid synthesis pathways.